Causal Effect of Visceral Adipose Tissue Accumulation on the Human Longevity: A Mendelian Randomization Study - Yan, Bin; Yang, Jian; Zhao, Binbin; Wu, Yanhua; Bai, Ling; Ma, Xiancang (Frontiers in Endocrinology, 2021)
Objective: Observational studies have demonstrated a close relationship between obesity and longevity. The aim of this Mendelian randomization (MR) study is to investigate whether genetic determinants of visceral adipose tissue (VAT) accumulation is causally associated with longevity. Methods: In this two-sample Mendelian randomization (MR) study, we used summary data of genetic determinants (single nucleotide polymorphisms; P < 5 × 10-8) of VAT accumulation based on genome-wide association studies (GWAS). Longevity was defined as an age beyond the 90th or 99th survival percentile. The causal association of VAT accumulation with longevity was estimated with the inverse variance weighted (IVW) method. Sensitivity analyses, including weighted median, MR-Egger and MR- pleiotropy residual sum and outlier (PRESSO), were also employed to assess the stability of the IVW results. Results: Our MR analysis used 221 genetic variants as instrumental variables to explore the causal association between VAT accumulation and longevity. In the standard IVW methods, VAT accumulation (per 1 kg increase) was found to be significantly associated with lower odds of surviving to the 90th (odds ratio [OR] = 0.69; 95% confidence interval [CI] 0.55 to 0.86, P = 8.32 × 10-4) and 99th (OR = 0.67; 95% CI 0.49 to 0.91, P = 0.011) percentile age. These findings remained stable in sensitivity analysis. Conclusion: This MR analysis identified a causal relationship between genetically determined VAT accumulation and longevity, suggesting that visceral adiposity may have a negative effect on longevity.